Time-Dependence of Mechanical Property Alterations on Anthracite Coals Treated by Supercritical Carbon Dioxide. (28th October 2019) - Li, Wei; Pang, Bin; Su, Er-lei; Yang, Quanlin; Liu, Qingquan; Cheng, Yuanping
Abstract : The injection of supercritical carbon dioxide (Sc-CO2 ) into coal seams remarkably changes the physical-chemical structures of coal mass and thereby improves coal mechanical properties. In this study, a series of unconfined and triaxial compressive strength tests were performed on anthracite coal samples under the pressure of 8 MPa at the temperature of 35°C for 24 h and 48 h, respectively. Besides, experiments with longer Sc-CO2 treatment time were carried out on coal mass without stress constraint to observe the damage mode of coal. The results show that Sc-CO2 treatment obviously alters time-dependent mechanical properties of anthracite coal. The coal samples treated with Sc-CO2 for 240 h and 960 h show different damage modes from limited fractures to a complicated fracture network. The time-dependence of the mechanical weakening model on Sc-CO2 -treated coal was proposed to explain the link between CO2 flow and mechanical weakening effect by means of physical-chemical effects on time scales.